2013
DOI: 10.1161/hypertensionaha.111.00439
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic Clamp Insulin Sensitivity and Longitudinal Systolic Blood Pressure

Abstract: Abstract-Insulin resistance may be an independent risk factor for the development of hypertension, but change in blood pressure (BP) over time has not been adequately studied in healthy individuals fully characterized for insulin sensitivity.In the Relationship between Insulin Sensitivity and Cardiovascular disease (RISC) study, we measured insulin sensitivity (M/I) using the euglycemic clamp technique in 1073 healthy European adults (587 women, 486 men) aged 30 to 60 years followed up 3 years later. Systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Interestingly, our data show that the II ACE genotype increases the risk of central adiposity-mediated hypertension, despite the favorable metabolic characteristics observed in these patients, which are described both in previous reports 45 and our data. We hypothesize that the possible explanation may lie in the increased salt sensitivity found in the II genotype, with mechanisms that are still unclear and that, based on our findings, are likely to overcome the independent effect of a small difference in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, our data show that the II ACE genotype increases the risk of central adiposity-mediated hypertension, despite the favorable metabolic characteristics observed in these patients, which are described both in previous reports 45 and our data. We hypothesize that the possible explanation may lie in the increased salt sensitivity found in the II genotype, with mechanisms that are still unclear and that, based on our findings, are likely to overcome the independent effect of a small difference in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…This higher impact of IR on hypertension risk among women compared to men, was recently addressed in a meta-analysis conducted by Feng Wangs et al [27], showing an independent association between fasting insulin as well as IR with a more pronounced risk of hypertension, in women (relative risk (RR) 2.07; 95% CI 1.19–3.60) than in men (RR 1.48; 95% CI 1.17–1.88). Likewise, the study conducted by Petrie et al [28] showed that in women (but not men) low insulin sensitivity, measured by the euglycemic clamp technique, was associated with higher levels of SBP over time, independent of key covariates including age, baseline blood pressure, BMI and change in BMI. The higher impact of IR in the development of hypertension among women, might be attributable to the effect of lower lean body mass in women; hence, fasting insulin or HOMA-IR values in women reflect a higher level of tissue IR [28].…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, the study conducted by Petrie et al [28] showed that in women (but not men) low insulin sensitivity, measured by the euglycemic clamp technique, was associated with higher levels of SBP over time, independent of key covariates including age, baseline blood pressure, BMI and change in BMI. The higher impact of IR in the development of hypertension among women, might be attributable to the effect of lower lean body mass in women; hence, fasting insulin or HOMA-IR values in women reflect a higher level of tissue IR [28]. On the other hand, other studies showed similar or higher impact of IR among men rather than women [29, 30].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the presence of any of the components of metabolic syndrome appears to pose a much greater risk to health in women than in men. Indeed, (i) obesity increases inflammatory markers and is a more prominent risk factor for type 2 diabetes in women than in men ; (ii) type 2 diabetes confers a much higher risk of cardiovascular‐related mortality and is more frequently characterized by postprandial hyperglycaemia in women than in men and (iii) low insulin sensitivity independently predicts longitudinal change in blood pressure in women but not in men .…”
Section: Introductionmentioning
confidence: 99%